Jurassic Park $h [videorecording] adventure pack - Crichton, Michael 1942; Kennedy, Kathleen 1954-; Molen, Gerald R; Universal Pictures (Firm) (cairo IHE, 2005)
Jurassic Park III: Eight years after the InGen incident, Dr. Grant is happy with his life far from any dinosaurs other than the fossilized ones. Unfortunately, he is extremely short in research money, and therefore accepts the offer from a wealthy businessman. Originally issued in 2001
Jurassic Park: Scientists develop a means of bringing dinosaurs to life using DNA taken from dino' blood, which has been preserved inside insects encased in amber. Originally issued in 1993
Lost world: Four years after the failure of Jurassic Park on Isla Nublar, it is revealed that there was another island ("Site B") on which dinosaurs were bred before being transported to Isla Nublar. Originally issued in 1997
Trilogy includes: Jurassic Park, Jurassic Park: The lost world; Jurassic Park III; bonus materials on each disc
Jurassic Park: Sam Neill, Laura Dern, Jeff Goldblum ; Lost world: Jeff Goldblum, Julianne Moore, Pete Postlethwaite ; Jurassic Park III: Sam Neill, William H. Macy, Te?a Leoni, Laura Dern
1 2
Keywords: Dinosaurs -- Drama; Paleontology $y Jurassic $v Drama; (3eGdJj ejOjG cHGQs -- (3ehGO SeYjI hHUQjIs